Pemenuhan Hak Restitusi Terhadap Anak Korban Tindak Pidana Pemerkosaan - Palijama, Pricilia Triana; Wadjo, Hadibah Zachra; Patty, Jetty Martje (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2025)
Introduction: Children are very vulnerable to becoming victims of criminal acts, especially victims of rape. Therefore, the government has issued various kinds of laws and regulations so that every child gets legal protection and gets their rights. One of them is Article 71D of Law 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection which explains that child victims have the right to apply to the court for restitution or compensation. However, in reality, restitution has not been implemented in every court decision so that child victims do not get their rights.Purposes of the Research:  examine and discuss mechanisms for fulfilling the right to restitution for children as victims of criminal acts of rape and obstacles in fulfilling the right to restitution for children as victims of criminal acts of rape.Methods of the Research: This research uses normative legal research methods based on primary and secondary legal materials and uses approaches: statutory approach, concept approach and case approach.Results / Findings / Novelty of the Research: The results of the research show that the mechanism for fulfilling restitution for child victims of criminal acts of rape is regulated in Government Regulation No. 43 of 2017 concerning the Implementation of Restitution for Children Who Are Victims of Crime. However, the implementation of restitution in various laws and regulations in Indonesia is still difficult to implement, this is due to the content of these laws and regulations, especially the mechanism for providing restitution, law enforcement, in which case investigators and public prosecutors are obliged to notify victims. to be able to apply for restitution. In fulfilling the right to restitution there are obstacles, namely law enforcement, the law itself, society, culture and the existence of accompanying institutions such as LPSK which do not yet exist in all provinces of Indonesia, including Maluku.